Hydrogen decreases susceptibility to AngII-induced atrial fibrillation and atrial fibrosis via the NOX4/ROS/NLRP3 and TGF-β1/Smad2/3 signaling pathways. - Binmei Zhang; Jingxiu Hou; Jiaren Liu; Junhui He; Yunan Gao; Guangnan Li; Tianjiao Ma; Xin Lv; Li Dong; Wei Yang (PLoS ONE)
Atrial fibrillation (AF) represents the commonly occurring cardiac arrhythmia and the main factor leading to stroke and heart failure. Hydrogen (H2) is a gaseous signaling molecule that has the effects of anti-inflammation and antioxidation. Our study provides evidence that hydrogen decreases susceptibility to AngII-mediated AF together with atrial fibrosis. Following continuous AngII administration for a 28-day period, AngII+H2 treated rats showed decreased susceptibility to AF, a decrease in atrial fibrosis, a decrease in ROS in atrial myocytes, an inhibition of NLRP3 inflammasome activation, an improvement in electrical remodeling, and an inhibition of proliferation and migration of cardiac fibroblasts. We further found that hydrogen regulates the activation of inflammasome and thus improves Ca2+ handling and IKAch and IKur by inhibiting the activity of NOX4 in vivo. In addition, hydrogen was involved in AngII-mediated atrial fibrosis through inhibiting TGF-β1/Smad2/3 pathway through suppressing TGF-β1 activation and secretion in vivo. Our findings suggest that hydrogen is important for preventing and treating AngII-mediated AF and atrial fibrosis, suggesting that hydrogen could be used as the candidate way to prevent and treat AF.